2002
DOI: 10.1055/s-2002-26705
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Improves Cardiac Functional Recovery After Ischemia in Rats

Abstract: The biguanide, metformin, is widely used for the treatment of type 2 diabetes mellitus. In the recently published United Kingdom Prospective Diabetes Study (UKPDS), it was shown that the use of metformin was associated with a reduction of macrovascular complications compared to other blood glucose-lowering strategies. The present study was aimed at determining whether metformin has direct beneficial effects on the heart. We tested the effects of metformin on cardiac functional recovery after a mild ischemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 7 publications
3
31
1
Order By: Relevance
“…Regarding dosage, 125 g/kg is 286-fold less than the maximum antihyperglycemic dose (2,500 mg/day) of metformin, making the current study the first to clearly demonstrate that a subtherapeutic dose of metformin can provide cardioprotection. Regarding the time of administration, we demonstrate that in contrast to previous studies (20,21), which reported the cardioprotective effects of a chronic administration or constant perfusion of metformin, an acute administration of metformin given once either before ischemia or at the time of reperfusion can provide protection. These findings are of clinical relevance since they demonstrate that acute metformin treatment could potentially be initiated at the time of coronary artery reperfusion to patients experiencing myocardial ischemia.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Regarding dosage, 125 g/kg is 286-fold less than the maximum antihyperglycemic dose (2,500 mg/day) of metformin, making the current study the first to clearly demonstrate that a subtherapeutic dose of metformin can provide cardioprotection. Regarding the time of administration, we demonstrate that in contrast to previous studies (20,21), which reported the cardioprotective effects of a chronic administration or constant perfusion of metformin, an acute administration of metformin given once either before ischemia or at the time of reperfusion can provide protection. These findings are of clinical relevance since they demonstrate that acute metformin treatment could potentially be initiated at the time of coronary artery reperfusion to patients experiencing myocardial ischemia.…”
Section: Discussioncontrasting
confidence: 89%
“…However, a closer look at the UKPDS studies reveals that metformin reduced A1C values in treated patients to the same extent as in the other cohort of patients treated with conventional therapies, suggesting that metformin might have additional cardioprotective actions beyond its antihyperglycemic effects (7). This notion is further supported by the observation that metformin does not affect glucose values in nondiabetic rodents (20) yet improves cardiac function following in vitro global ischemia (21). This is further supported by the findings of the current study, which is the first to provide strong evidence that a single administration of metformin to nondiabetic and diabetic mice profoundly reduces infarct size without lowering blood glucose levels.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For type-2 diabetics, oral agents (sulfonylurea or oral hypoglycemic agents, Metformin, DPP-4 inhibitors, SGLT-2 inhibitors, thiazolidinediones) can be used alone or in combination with insulin; these treatments can be shifted to insulin with metformin if they remain uncontrolled on oral agents. Metformin should be prescribed to type-2 diabetic patients (if not contraindicated) because metformin has cardiovascular protective effects, reduces insulin resistance, increases insulin sensitivity, and decreases the serum lipids while elevates HDL-C as has been demonstrated by research studies [63][64][65][66][67][68][69][70]. It is recommended following best available guidelines for the management of diabetes and its complications [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that several tissues endangered by oxidative imbalance associated with T2D, particularly the myocardium (38,44), endothelial cells (5,48), and the brain (13), could be protected by metformin administration. Surprisingly, there are scarce data regarding the antioxidant effect of metformin in the fatty liver, despite the fact that steatosis is a hallmark of T2D and that the fatty liver is highly susceptible to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%